CEO and CSR Reporting: A Bibliometric Analysis - Widoretno, Astrini Aning; Azmiyanti, Rizdina (Akuntansi: Jurnal Akuntansi Integratif, 2025)
This study aims to examine previous studies related to the relationship between CEO power in the implementation of CSR in a company and explore how the characteristics of CEO power influence CSR, especially in non-financial companies in Indonesia with a period between 2020-2022 after the Covid pandemic -19. The method used in this study is a literature review by analyzing 21 articles that are relevant to the research topic raised. The analysis results stated that several previous studies revealed that CEO power had a negative relationshipwith a company's CSR disclosure level. In addition, CEO duality and CSR disclosure also has a negative relationship, where CEO duality will reduce the CEO's responsibility to stakeholders, which can weaken CSR performance in a company. This analysis explains that the relationship between CEO Power in implementing CSR is limited to manufacturing and mining companies and is rarely discussed regarding non-financial companies.